The cybercriminal risks and threats of body-hacking crimes under the legal framework of Budapest Convention - Demirezici, Ahmet Sami (Bioethica, 2025)
In this Article, the Budapest Convention (The Convention on Cybercrime, Council of Europe, ETS No. 185) is put under legal analysis in the scope of risks and threats of cybercrimes against implantable, prosthetic and medical devices, referred to as “Body-Hacking Crimes” according to the terminology of this research. To analyze the Budapest Convention systematically, the risks and threats of “Body-Hacking Crimes” are brought to light under three sub-headings (Body-Hacking, Elements of Cybercrimes, Crimes & Reservations) as the main subjects of this Article. Under the first sub-heading, the term “Body-Hacking” is defined and explained as regards of its usage in the general and criminological literature to describe a new category of cybercrimes, as classified “Body-Hacking Crimes” in this paper. Under the second sub-heading, the elements of cybercrimes are analyzed in regard to the substantive law and human rights provisions of the Budapest Convention and legal loopholes regarding body-hacking crimes are uncovered in these provisions. Though there are multiple elements of cybercrimes required to be analyzed in specific to body-hacking crimes, only three elements (Intention, Non-Authorization, Computer Systems) are evaluated under the second sub-heading due to the inadequate regulations and definitions of these elements in the Budapest Convention. Under the final and third sub-heading, computer-related crimes and reservations regulated in the Budapest Convention are examined in correlation with the hackable nature of implantable, prosthetic and medical devices. Particularly, bodily integrity crimes are brought into the focus for legal analysis of body-hacking crimes inducing bodily damage in the final part of this article. In this study, the substantive-law-oriented and definitional problems of the Budapest Convention are predominantly investigated, which results in pointing out mostly Articles 1-13 of Budapest Convention. Furthermore, the domestic laws and court verdicts, esp. UK, US, France and Dutch cybercrime laws and supreme court decisions, are referred in this study to provide a legal perspective regarding the development of body-hacking crimes in the national legislations.